Prepontine Schwannoma Presenting With Atypical Facial Symptoms - A Case Report - Rishi Kumar Bali; Aruna V Singh; Zarina Bajaj (Wolters Kluwer Medknow Publications, 2005)
Face is an important landmark and any pathological condition affecting it has tremendous bearing on psychological make up of the patient. This report describes a rare case of a young female who presented with Hemifacial dysaesthesia complicated by ipsilateral masticatory complex dyskinesia.